A New Game Plan for Concussion Education. (December 2019) - Kroshus, Emily; Chrisman, Sara P. D.
Despite state laws requiring concussion education for youth sport stakeholders and a proliferation of educational programs, there has been little demonstrated impact on concussion reporting behaviors. We propose that this is because of four key limitations to existing approaches to concussion education: (1) deliberative decision making by the injured athlete is assumed, (2) interventions are often targeted at individuals rather than social systems, (3) education occurs once during preseason and is forgotten, and (4) dissemination challenges exacerbate health inequalities. Addressing these limitations, we propose a novel theoretic framework that situates individual behavior within a sport system's culture and their broader structural context. Concussion education programs should seek to facilitate safety-supportive interpersonal communication within and between stakeholder groups and influence attributes of groups that drive behavior, including shared values. Addressing the limitations outlined and drawing on the proposed conceptual framework, we describe a novel approach to concussion education: pregame safety huddles.